DAMPAK KONVERGENSI STANDAR AKUNTANSI KEUANGAN TERHADAP INTERNATIONAL FINANCIAL REPORTING STANDARDS ( IFRS ) PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA ( STUDI KASUS PERUSAHAAN MANUFAKTUR ) (Proceeding Fakultas Ekonomi, 2014)
This paper aims to reveal how the effect of Financial Accounting Standards converged to International Financial Reporting Standards (IFRS) to the companies listed in Indonesia Stock Exchange that includes: 1. How does the adherence to the new accounting standard applicable; 2. How does the application of a new accounting standard applicable to the financial statements; 3. Standards of financial accounting newly enacted what impact the company's financial statements. This study is a descriptive study with popolasi companies listed in Indonesia Stock Exchange. Companies sampled in this study is a company registered in the Indonesian Capital Market Directory ( ICMD ) in 2012 as many as 146 companies and has the financial report in 2012 which can be accessed memalui www.idx.co.id. This is done with the consideration that the company has made a financial statement that ends the previous year in 2011 so it will be able to distinguish and evaluate the impact of the adoption of new accounting standards in the preparation of financial statements of companies that ended in 2012. Based on the sample criteria manufacturing company sampled in this study were as many as 84 companies and the remaining 62 companies did not meet the criteria. To investigate the effect of the application of accounting standards on the financial statements as a descriptive analysis of the statements contained in the Notes to the Financial Statements companies sampled. The study found that: 1. Entire sample companies comply with the new accounting standards as a guide in the preparation of financial statements ending in 2012; 2. Samples from 84 companies stated that the application of the new accounting standards significantly affect financial reporting as many as 33 companies, while 55 companies expressed no significant effect; 3. New financial accounting standards the most effect on the financial statements is PSAK No.. 60 that affect the 30 companies, PSAK No.. 24 effect on 12 companies, and PSAK No. 9,10 affect the company, while the other is the effect of PSAK smaller. Keywords: Convergence, Quality of Financial Statements, comparability